Mediating role of online academic emotions between online presence and learning performance in blended learning environments - Xingqiao Li; Yinghua Ye (Scientific Reports)
Abstract Blended learning has been widely used and popularized in recent years. It was originally designed to create a highly engaging learning experience for students; however, in practice, it often falls short. In particular, online learning within blended learning environments suffers from a lack or inadequacy of online presence, which is likely to trigger students’ negative academic emotions during online learning, leading to poor learning outcomes. However, the impact of online academic emotions on learning performance in blended learning has received little attention in empirical studies. This study examines the relationships among online academic emotions, online presence, and learning performance in blended learning. A stratified sampling questionnaire was used to survey 1,192 college and university students, and 971 valid questionnaires were returned. Through descriptive and correlational analyses of each research variable, the predictive relationships among the variables and the mediating effect of online academic emotions in the process of influencing online presence on blended learning performance were explored. The findings indicate that online presence significantly positively predicts positive online academic emotions and significantly negatively predicts negative online academic emotions in a blended learning environment. Online presence has a positive predictive effect on learning performance, and positive-low arousal academic emotions (calmness and relaxation) partially mediate the relationship between online presence and learning performance. This study may encourage instructors to emphasize the impact of online academic emotions on learning performance.